Development of an evidence-based complementary feeding practice module for mothers using the combined Delphi Method - Rini Andriani; Damayanti Rusli Sjarif; Bambang Supriyatno; Aria Kekalih; Hartono Gunardi; Ika Karlina Idris (Paediatrica Indonesiana, 2022)
Background Malnutrition in infants remains a challenge in Indonesia. Malnutrition often arises as a result of errors in complementary feeding practices. An education module for Indonesian mothers may help them correctly implement complementary feeding practices.